Large decadal scale changes of polar ozone suggest solar influence - B.-M. Sinnhuber; P. von der Gathen; M. Sinnhuber; M. Rex; G. König-Langlo; S. J. Oltmans (Atmospheric Chemistry and Physics, 2006)
Long-term measurements of polar ozone show an unexpectedly large decadal scale variability in the mid-stratosphere during winter. Negative ozone anomalies are strongly correlated with the flux of energetic electrons in the radiation belt, which is modulated by the 11-year solar cycle. The magnitude of the observed decadal ozone changes (≈20%) is much larger than any previously reported solar cycle effect in the atmosphere up to this altitude. The early-winter ozone anomalies subsequently propagate downward into the lower stratosphere and may even influence total ozone and meteorological conditions during spring. These findings suggest a previously unrecognized mechanism by which solar variability impacts on climate through changes in polar ozone.